Preliminary study towards a novel experimental model to study localized cutaneous leishmaniasis caused bY Leishmania (Leishmania) mexicana - Sosa-Bibiano, Erika Ivett; Wynsberghe, Nicole Raymonde Van; Canto-Lara, Silvia Beatriz; Andrade-Narvaez, Fernando Jose (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
There is not an experimental model of localized cutaneous leishmaniasis (LCL) caused by Leishmania (Leishmania) mexicana. The aim of the present study was to characterize the clinical and histological features of Peromyscus yucatanicus experimentally infected with L. (L.) mexicana. A total of 54 P. yucatanicus (groups of 18) were inoculated with 1x10(6) promastigotes of L. (L.) mexicana in the base of the tail. They were euthanized at three and six months post experimental infection. The control group was inoculated with RPMI-1640. The predominant clinical sign observed was a single ulcerated lesion in 27.77% (5/18) and in 11.11% (2/18) P. yucatanicus at three and six months respectively. The histological pattern described as chronic granulomatous inflammation with or without necrosis was found in 7/7 (100%) biopsies of euthanized P. yucatanicus at three (n = 5) and six (n = 2) months, respectively. These results resembled clinical and histological features caused by L. (L.) mexicana in humans, and support the possibility to employ P. yucatanicus as a novel experimental model to study LCL caused by this parasite.